Anthropogenic aerosol effects on East Asian winter monsoon: The role of black carbon‐induced Tibetan Plateau warming. Issue 11 (14th June 2017) - Jiang, Yiquan; Yang, Xiu‐Qun; Liu, Xiaohong; Yang, Dejian; Sun, Xuguang; Wang, Minghuai; Ding, Aijun; Wang, Tijian; Fu, Congbin
Abstract: This study investigates anthropogenic aerosol effects on East Asian winter monsoon (EAWM) with Community Atmospheric Model version 5. In winter, the anthropogenic aerosol optical depth is the largest over southern East Asia and adjacent oceans. The associated EAWM change, however, is the most significant in northern East Asia, which is characterized by a significant surface cooling in northern East Asia and an acceleration of the jet stream around 40°N, indicating an intensification of the EAWM northern mode. Such an intensification is attributed to anthropogenic black carbon (BC)‐induced Tibetan Plateau (TP) warming. The BC is mostly transported from northern South Asia by wintertime westerly and southwesterly and then deposited on snow, giving rise to a reduction of surface albedo and an increase of surface air temperature via the snow‐albedo feedback. The TP warming increases meridional temperature gradient and lower tropospheric baroclinicity over northern East Asia, leading to the jet stream acceleration around 40°N and the westward shift of East Asian major trough via the transient eddy‐mean flow feedback. Such upper tropospheric pattern favors more cold air outbreak, leading to a large surface cooling in northern East Asia. In southern East Asia, the effect of nonabsorbing aerosols is dominant. The solar flux at surface is significantly reduced directly by scattering of nonabsorbing aerosols and indirectly by intensification of short wave cloud forcing. Accordingly, the surface air temperature in southern East Asia is reduced. The precipitation is also significantly reduced in South China and Indo‐China Peninsula, where the aerosol indirect effect is the largest. Key Points: Anthropogenic aerosol optical depth is the largest over southern East Asia during winter Black carbon‐induced Tibetan Plateau warming intensifies the northern mode of East Asian winter monsoon Nonabsorbing aerosols decrease surface air temperature and precipitation in southern East Asia